Pengaruh Servicescape Dan Perceived Value Terhadap Repurchase Intention Di Hotel Balairung Jakarta - Risti Widya Ningrum; Hijriyantomi Suyuthie (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This research discusses the influence of Servicescape and Perceived Value on Repurchase Intention at Hotel Balairung Jakarta, which is based on guest reviews on Google Review, Tiket.com and Traveloka regarding Hotel Balairung Jakarta. This research purpose to reveal the Servicescape and Perceived Value influence on Repurchase Intention at Hotel Balairung Jakarta. The research type used was quantitative descriptive with a causal associative approach, the sampling technique used purposive sampling which was applied to 317 respondents. The technique for data collection uses a questionnaire with a Likert scale which has been tested for validity and reliability. The technique for data analysis including of data description, analysis requirements test with test of normality, heteroscedasticity and multicollinearity as well as hypothesis testing with multiple linear regression tests using SPSS version 26.00.